EVALUASI KEMANDIRIAN BELAJAR - Halimatussa’diyah (CV. ADIBA AISHA AMIRA, 2023)
Independence can be understood as self-directed learning, namely how individuals learn by having initiative in learning, analyzing their own learning needs, finding sources of independent learning, and formulating their own learning objectives, making choices and implementing learning strategies as well as conducting self-evaluations. Learning independence can be concluded as an active, constructive process when students are able to set learning goals and effort in monitoring, regulation, controlling cognition, motivation, as well as their behavior that leads to goals and is contextualized in the environment. Carry out the process of measuring the independence of an individual with the aim of knowing with certainty and detail. This assessment is carried out using observation techniques, individual assessments, peer assessments, and assessment journals.